Modification Fisher Rebuilding Intervention and ‘Sabar’ Counseling on Women after Divorced - Hasibuan, Wilda; Adiningtiyas, Sri Wahyuni; Hadiyanto, Alwan; Asanjarani, Faramarz (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2024)
A divorce is not something that every couple wants. No couple must desire divorce if there are still opportunities. The primary issues in many divorces, including those involving community service, are The methods utilized in the home to resolve disputes, the coping mechanisms employed in times of stress, and the personalities of each couple. Three distinct divorce situations were treated using the Fisher Rebuilding Intervention and 'Sabar' Counselling as a result of this service. The outcome of this service is that the SP case finds a way to deal with long-buried emotions, the VN case has no emotional content and allows for more behavioral interventions, and in the ST case, the angler rebuilding intervention is not only carried out on ST but also on his daughter and his daughter's adolescent.